Sequential sampling plant of damage caused by Perileucoptera coffeella in Paraná - Villacorta, A.; Tornero, M. T.T. (Pesquisa Agropecuaria Brasileira, 2014)
Outbreaks of coffee leaf miner Perileucoptera coffeella (Guerin-Meneville, 1842) (Lepidoptera, Lyonetiidae) that occurred during the years 1977 and 1978 caused considerable damage to coffee plantations in Paraná State, Brazil. The development of the sequential sampling technique was choosed for use in pest management, to take decision on the need of insecticide applications to control coffee leaf miner. A samplig technique, probabilistic models and parameter estimation techniques used in this study are described. A sequential sampling plan is presented based on mines per leave. The significance level was 10%, and the confidence level, 90%.